2021
DOI: 10.1177/08853282211027882
|View full text |Cite
|
Sign up to set email alerts
|

Emerging self-assembling peptide nanomaterial for anti-cancer therapy

Abstract: Recently it is mainly focused on anti-tumor comprehensive treatments like finding target tumor cells or activating immune cells to inhibit tumor recurrence and metastasis. At present, chemotherapy and molecular-targeted drugs can inhibit tumor cell growth to a certain extent. However, multi-drug resistance and immune escape often make it difficult for new drugs to achieve expected effects. Peptide hydrogel nanoparticles is a new type of biological material with functional peptide chains as the core and self-as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 228 publications
(263 reference statements)
0
5
0
Order By: Relevance
“…Due to their adhesion, 37 biocompatibility, 38 and biodegradation, 39,40 peptides have been widely used in cell culture, 41 tissue engineering, 42,43 and local delivery of various drugs/genes. 44,45 Our experiments showed that RLDI and RQDT can continuously and stably release antigens, which provides a reliable basis for continuous and stable T-cell stimulation to produce specific immune responses when DC vaccines are injected into mice. Several problems with DC vaccines have been optimized and explored here.…”
Section: Discussionmentioning
confidence: 88%
“…Due to their adhesion, 37 biocompatibility, 38 and biodegradation, 39,40 peptides have been widely used in cell culture, 41 tissue engineering, 42,43 and local delivery of various drugs/genes. 44,45 Our experiments showed that RLDI and RQDT can continuously and stably release antigens, which provides a reliable basis for continuous and stable T-cell stimulation to produce specific immune responses when DC vaccines are injected into mice. Several problems with DC vaccines have been optimized and explored here.…”
Section: Discussionmentioning
confidence: 88%
“…Self-assembling peptides (SAPs) are small biomedical materials that can also function as an effective drug delivery system to deliver antigens to cancer cells [ 80 , 81 ]. SAPs can be manufactured to form various constructions such as nanomicelles, nanotubes, nanovesicles, nanotapes, and hydrogels [ 80 ].…”
Section: Dna Vaccine Delivery Platformsmentioning
confidence: 99%
“…This innovative delivery system has several advantages compared to liposomes or nanoparticles, such as high drug-loading efficiency, low drug leakage, easier uptake, and highly biodegradable properties [ 63 ]. Additionally, it can induce long-time immune response in an adjuvant independent manner [ 81 ]. Recently, an interesting study showed that a new delivery platform based on SAPs, called the Glycosaminoglycan (GAG)-binding enhanced transduction (GET), was able to promote delivery of nucleic acids for gene therapy in lung organs [ 82 ].…”
Section: Dna Vaccine Delivery Platformsmentioning
confidence: 99%
“…Peptides display many different biological functions [74]. Assemblies formed from immune active peptides possess immunoregulatory features, immune checkpoint blocking (ICB) effect, antigen function, or self-adjuvanticity.…”
Section: Immune Active Peptide Self-assemblymentioning
confidence: 99%